Effect of dietary protein levels in growth performance of ostrich chicks during 2–10 weeks of age - Al Suwaye, Wjdan Ayad Abdlnabi (Journal of agricultural, environmental and veterinary sciences, 2018)
The present work was conducted to examine the effects of adding different concentrations of dietary crude protein (CP) (18, and 21%) on the growth performance parameters of the ostrich chicks that include; the initial and final body weight, daily body weight gain, feed consumption, feed conversion and the protein efficiency ratio during the period from2-10 weeks of age. A total of twenty African Black unsexed ostrich chicks were used in the present study in a simple randomized design and these birds were divided into two groups with ten birds per each group. The first group was feed with diet containing 18 % of the CP, while the second group was feed with diet containing 21 % of the CP. The results of the present work indicated that the initial and final live body weight, body weight gain, feed consumption, and feed conversion of ostrich chicks were non-significantly affected by different concentration of the dietary CP that was used. Whereas, the results showed that there was a significant increase in the protein efficiency ratio in the first group in comparison with the second group. In conclusion, the results of the present study indicated that feeding of the ostrich chicks with the diet that containing different concentrations of the CP did not effect on the growth parameters, but it showed the best protein efficiency ratio with the diet that contained the lower levels of the CP